Macroeconomics for MBAs and masters of finance - Davis, Morris A. 1972- (Cambridge University Press, 2009)
"Using a rigorous and concise framework, this book teaches the foundations ofmodernmacroeconomic theory and its methods. It is ideally suited for students taking a first graduate course inmacroeconomics as part of anMBA, finance, or economics degree. The book explains recent advances of modern macroeconomic theorywith respect to growth, business cycles, and asset pricing by focusing on aspects of firmand household behavior that are embedded in modern macroeconomic studies. Throughout the book data issues are discussed in detail:where to find the data, howto download it, and the correspondence of datawithmodelpredictions.Themathematical level assumes that students have taken a course in calculus.With its emphasis on dynamic intertemporalmacroeconomics and the use of data, the book provides studentswith a core toolkit thatwill equip them both for more advanced study and for professional careers as economists. Additional resources (including PowerPoint slides for each chapter, detailed answers to all the questions in the book, and links to useful sites) are available online atwww.cambridge.org/macro4mba"--Provided by publisher.
"Using a rigorous and concise framework, this book teaches the foundations ofmodernmacroeconomic theory and its methods. It is ideally suited for students taking a first graduate course inmacroeconomics as part of anMBA, finance, or economics degree. The book explains recent advances of modern macroeconomic theorywith respect to growth, business cycles, and asset pricing by focusing on aspects of firmand household behavior that are embedded in modern macroeconomic studies. Throughout the book data issues are discussed in detail:where to find the data, howto download it, and the correspondence of datawithmodelpredictions.Themathematical level assumes that students have taken a course in calculus.With its emphasis on dynamic intertemporalmacroeconomics and the use of data, the book provides studentswith a core toolkit thatwill equip them both for more advanced study and for professional careers as economists. Additional resources (including PowerPoint slides for each chapter, detailed answers to all the questions in the book, and links to useful sites) are available online atwww.cambridge.org/macro4mba"--Provided by publisher.
Includes bibliographical references and index
Keywords: Macroeconomics; Makroökonomie